ANALISIS PROSES BERPIKIR MATEMATIS MAHASISWA DALAM MENYELESAIKAN MASALAH STATISTIKA - Herlina, Sari; Wahyuni, Reni; Juandi, Dadang; Putri, Finola Marta (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2023)
AbstractEach student has a different mathematical thinking process in solving mathematical problems. This study aims to assess the mathematical thinking process of students in solving statistical problems. The subjects of the study were taken by purposive sampling. The subject of the study was 6 students of Islamic Religious Education student who took the fifth semester with high, medium, and low abilities. The instrument used is a ters sheet on statistical material. Data collection techniques through statistical question tests on research data sampling sub-materials. Data analysis was carried out in a qualitative descriptive manner. The analysis was conducted through answer sheets of each study subject looking at thought processes based on steps in Bransford and Stein's approach. The results showed that high-ability students tend to have conceptual mathematical thinking processes, moderately capable students tend to have mathematical thinking process abilities in semiconceptual groups, while low-ability students tend to have competitive mathematical thinking processes. Abstrak Setiap mahasiswa mempunyai proses berpikir matematis berbeda-beda dalam menyelesaikan permasalahan matematika. Penelitian ini bertujuan untuk menilai proses berpikir matematis mahasiswa dalam memecahkan masalah statistika. Subjek penelitian diambil secara purposive sampling. Subjek penelitian merupakan 6 orang mahasiswa Pendidikan Agama Islam yang menempuh semester lima tahun ajaran 2023-2024 dengan kemampuan tinggi, sedang, dan rendah. Instrumen yang digunakan adalah lembar tes pada materi statistika. Teknik pengumpulan data melalui tes soal statistika pada sub-materi pengambilan sampel data penelitian. Analisis data dilakukan secara deskriptif kualitatif melalui lembar jawaban setiap subjek penelitian dengan melihat proses berpikir berdasarkan langkah-langkah dalam pendekatan Bransford dan Stein. Hasil penelitian menunjukkan bahwa mahasiswa yang berkemampuan tinggi cenderung mempunyai proses berpikir matematis konseptual, mahasiswa yang berkemampuan sedang cenderung mempunyai kemampuan proses berpikir matematis dalam kelompok semikonseptual, dan mahasiswa yang berkemampuan rendah cenderung proses berpikir matematis komputasional